Habib Dan Pengembangan Keagamaan Masyarakat Perkotaan (Peran dan fungsi Habib Syarif Muhammad Al-‘Aydrus di Kota Bandung) - Saepudin, Ahmad (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2018)
The purpose of writing this article is to describe the social role of Habib's diversity in the dynamics of the diversity of urban communities, especially in Bandung. Through descriptive methods, analysis of data obtained from interviews and observations has shown that when identity is able to enter the realm of religion, based on the strength of religious roles, it is able to deliver to a very strong position. The style of the role run by Habib Syarif as a research subject shows a moderate religious role, besides being able to maintain local Islamic traditions. In addition, Habib has a meaning and a clan that is quite strong in the eyes of the clergy and the community. This is an attraction for pilgrims to get involved and participate in religious activities in urban areas.